(untitled) (Research, Society and Development, 2022)
This work has as its theme the use of PowerPoint (PPT) as a technological resource to be used by the teacher to build games for the diversification of Portuguese Language classes as L2, in bilingual education (Libras-Portuguese language), offered to deaf students in the country (Brasil, 2015; Brasil, 2021). Our proposal is part of a time marked by the scarcity of materials and policies that guide the education of the deaf. Often included in mixed classes (with deaf and hearing people), these students receive decontextualized content that does not explore their learning potential through the visuospatial channel (Silva et al., 2018; Rodrigues, 2018). Based on a qualitative research, we carried out a bibliographic review that integrates knowledge about the education of the deaf and the use of gamification as an educational resource, seeking to question: what is the potential of games for teaching Portuguese for deaf students enrolled in Elementary School I? Is it possible to develop, with limited resources, material based on the educational specificities of these students? Seeking to answer these questions We developed and presented a Quis, developed based on the PowerPoint software. To exemplify the assembly and operation of the game, we thematized in our material the teaching of facial expressions, an important parameter for the formation of signs in Libras. We conclude by emphasizing the importance of building materials and offering adequate training to teachers, focused on strategies of this type, in view of the importance of improving the use of PowerPoint as a simple and versatile tool for the construction of educational resource games, diversifying classes and providing students with the use of technological tools.